PERCEPTION OF UNDERGRADUATE STUDENTS OF S.V. AGRICULTURAL COLLEGE REGARDING ONLINE CLASSES DURING THE COVID-19 PANDEMIC - P. BALA HUSSAIN REDDY*, V. SAILAJA; S.V.PRASAD (The Journal of Research ANGRAU, 2020)
The online survey was conducted between June, 2020 and August, 2020 to understand the perception of the undergraduate students of the S.V. Agricultural College, Tirupati regarding online classes. Out of 300 undergraduate students pursuing 1st, 2nd, and 3rd year of B.Sc (Hons.), 72 students belonging to all three years responded. The perception of the students was categorised under four aspects viz., perception of learning environment, social perception, academic self-perception and perception of students on faculty members.The majority of the students (97.1%) were using smartphone for attending virtual classes, ranked online lecture supported by a screen shared PowerPoint as the best virtual teaching method with a weightage of 278 and 3 hrs/day was the comfortable screen time mentioned by 50 percent of the students. About 95.7 percent of the students perceived that a real class environment helps in good understanding than an online learning environment. The majority (87.2%) stated that learning in isolation is not exciting.Less than half (44.10 %) of respondents expressed satisfaction, while 55.90% of the respondents expressed dissatisfaction towards virtual classes.